From Picturebooks to Play: Dialogic Pedagogy for Cultivating Agency and Social Awareness in Young Learners - Amanda Deliman (Education Sciences, 2025)
This study examines how young children engage with picturebooks, discussion, dramatic inquiry, and writing to negotiate diverse perspectives and develop empathy in an early childhood classroom. Grounded in sociocultural and critical literacy theories, the research explores the role of dialogic pedagogy in fostering young learners’ agency and social awareness. Utilizing a qualitative single-case study design, data were collected over a full academic year in a second-grade classroom through video recordings, field notes, interviews, and student artifacts. Thematic analysis revealed that dialogic engagements supported students in developing a shared language about empathy, resolving classroom conflicts, and exploring actionable ways to support others through collaborative play and inquiry. Findings highlight how sustained, student-driven inquiry fosters critical reflection and social responsibility, offering pedagogical insights into designing literacy experiences that nurture empathy, agency, and collective action. Implications for integrating dialogic literacy practices into early childhood education are discussed.